2013
DOI: 10.5539/jedp.v3n2p193
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ADHD Markers and Self-Perceived Stress: Influences on Academic Performance in Preadolescents

Abstract: The symptoms associated with Attention Deficit with Hyperactivity Disorder (ADHD), included in its different specific subtypes involves cognitive, emotional and behavioral changes leading to relationship and learning difficulties in school settings. Likewise, the impact of stress on academic performance, perceived by the students themselves on various life aspects, has been detected. A sampling of primary school pupils underwent the following tests: Testing Perception of Differences (Faces-R), Children Daily S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A meta-analysis 2 indicated that the worldwide prevalence of the disorder in children and adolescents is 5.29%. The symptoms that characterize ADHD, inattention, impulsivity or hyperactivity, can impair the social, academic or professional life of children, adolescents or adults diagnosed with the disorder, which causes a frequent search for specialized clinical care 3 and low school performance 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis 2 indicated that the worldwide prevalence of the disorder in children and adolescents is 5.29%. The symptoms that characterize ADHD, inattention, impulsivity or hyperactivity, can impair the social, academic or professional life of children, adolescents or adults diagnosed with the disorder, which causes a frequent search for specialized clinical care 3 and low school performance 4,5 .…”
Section: Introductionmentioning
confidence: 99%